Under the battle of Miraflores: The family as the basis of history - Valeriano Rodríguez, Héctor Alexander (2022)
Under the Battle of Miraflores (2012), is the first play written by the Peruvian playwright Paola Vicente Chocano (1977). Inspired by stories from her ancestors and taking the family as an example, Paola Vicente presents us with a drama, where fear, anxiety, anguish in the face of upcoming danger, will produce in its protagonists the courage to face sadness and disappointments, which present within the family nucleus. Set in the context of the Pacific War, it is a play where Peruvian women show their true courage to take the right actions and solve the problems they face.